Predictions of drying kinetics of aqueous droplets containing WPI-lactose and WPI-trehalose by application of composite reaction engineering approach (REA). (November 2016) - Haque, M. Amdadul; Adhikari, Benu; Putranto, Aditya
Abstract: Modelling of appropriate drying conditions is difficult due to the unavailability of drying kinetics. This problem becomes worse when the target materials contain multiple types of solutes. The present study attempted to develop and implement an effective model for predicting the important drying profiles (i.e. moisture content and drop temperature) of droplet which contains different types of solutes. Two different solutions of protein (whey protein isolate, WPI) and sugar (lactose and trehalose) were dried at single droplet level to validate the model. Aqueous droplets of protein and sugar solutions having 5 ± 0.1 μL volume (initial droplet diameter 2 ± 0.1 mm) were dried at two temperatures (65 °C and 80 °C) by using a custom-built single droplet dryer. In order to capture the effect of multiple solutes, the composite relative activation energies were developed and implemented to predict the drying profiles. It was found that, extension of reaction engineering approach (REA) to composite REA was accurate to model the drying profiles of aqueous droplets containing both protein and sugars. Hence, the composite REA is readily available for designing new processes and monitoring quality changes during drying of droplets which contain multiple different types of solutes. Highlights: Reaction Engineering Approach (REA) has successfully been extended to Composite REA. Composite REA effectively predicted the drying profiles of composite solution of different solutes. An empirical correlation successfully predicted the shrinkage of drying droplet.